Możliwości funkcjonalne chorych na stwardnienie rozsiane w zależności od czasu trwania choroby = Estimation of functionality of the patients suffering from multiple sclerosis depending on duration of illness - Mickiewicz, Piotr; Garczyński, Wojciech (Journal of Education, Health and Sport, 2016)
Mickiewicz Piotr, Garczyński Wojciech. Możliwości funkcjonalne chorych na stwardnienie rozsiane w zależności od czasu trwania choroby = Estimation of functionality of the patients suffering from multiple sclerosis depending on duration of illness. Journal of Education, Health and Sport. 2016;6(9):757-771. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159300 http://ojs.ukw.edu.pl/index.php/johs/article/view/3898 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. Możliwości funkcjonalne chorych na stwardnienie rozsiane w zależności od czasu trwania choroby Estimation of functionality of the patients suffering from multiple sclerosis depending on duration of illness Piotr Mickiewicz1 A,B,D-F, Wojciech Garczyński2,3 A 1 absolwent Wyższej Szkoły Edukacji i Terapii w Poznaniu 2 Wyższa Szkoła Edukacji i Terapii w Poznaniu, Wydział Studiów Edukacyjnych 3 Indywidualna Praktyka Fizjoterapeutyczna w Szczecinie A. przygotowanie projektu badawczego; B. zbieranie danych; C. analiza statystyczna; D. interpretacja danych; E. przygotowanie manuskryptu; F. opracowanie piśmiennictwa: G. pozyskanie funduszy. Słowa kluczowe: stwardnienie rozsiane, czas trwania choroby, sprawność, rehabilitacja Key words: multiple sclerosis, disease duration, efficiency, rehabilitation Wstęp. Stwardnienie rozsiane jest chorobą przewlekłą, postępującą i dokonującą nieodwracalnych zmian w obrębie układu nerwowego. Dotyczy ona najczęściej ludzi młodych i choruje na nią ponad 2,5 mln ludzi na całym świecie. Można wyróżnić pięć form klinicznych stwardnienia rozsianego, które objawiają się u pacjentów pod postacią charakterystycznych objawów. Rzuty choroby mają negatywny wpływ na sprawność fizyczną i psychiczną pacjentów, co może utrudniać ich funkcjonowanie. Cel pracy. Ocena możliwości funkcjonalnych pacjentów chorych na stwardnienie rozsiane w zależności od czasu trwania choroby. Materiał i metody. Badanie zostało przeprowadzone w kwietniu 2016 roku wśród pacjentów chorych na stwardnienie rozsiane, zakwalifikowanych do programów klinicznych Oddziału Neurologii Samodzielnego Publicznego Wojewódzkiego Szpitala Zespolonego przy ul Arkońskiej 4 w Szczecinie oraz Polskiego Towarzystwa Stwardnienia Rozsianego Oddziału Wojewódzkiego w Szczecinie. Badana grupa liczyła 40 osób (25 kobiet i 15 mężczyzn), średni wiek badanych wyniósł 45,5 lat ±13,22. Do oceny badanej grupy posłużył autorski kwestionariusz ankiety. Wyniki. W wyniku badań pacjenci zostali podzieleni na trzy grupy uwzględniające czas trwania choroby. Grupa A – chorujący do 5 lat, grupa B – chorujący od 6 do 15 lat i grupa C – chorujący powyżej 16 lat. Pacjenci chorujący do pięciu lat właściwie nie mają problemów z samodzielnym funkcjonowaniem. Pacjenci z grupy B i C największy problem mieli z poruszaniem się po schodach, 84,6% z nich nie jest w stanie poruszać się po nich samodzielnie. Zgięcie w stawie kolanowym w pozycji leżącej nie było w samodzielnie stanie wykonać 30,8% badanych z grupy B i 53,8% badanych z grupy C. Pomocy podczas chodzenia potrzebowało 30,8% badanych z grupy B i 23,1% z grupy C, natomiast samodzielnie nie poruszało się 38,5% badanych z grupy B i 46,6% badanych z grupy C. Wnioski. Uzyskane w badaniu wyniki potwierdzają, że czas trwania choroby może być brany pod uwagę przy ocenie funkcjonalnej osób chorych na stwardnienie rozsiane. Abstract: Multiple sclerosis is a chronic and progressive disease which makes irreversible changes in human nervous system. It concerns mostly young people and there are over 2,5 millions of people suffering from it all over the world. There are five clinical forms of multiple sclerosis which appear in the form of specific relapses. Relapses may have negative effect on patients’ physical and mental efficiency which may impede their functioning. Objectives: Estimation of functionality of the patients suffering from multiple sclerosis depending on duration of illness. Material and methods: The research was made in April 2016 among patients sick with multiple sclerosis, qualified for clinical programs of the Department of Neurology of the Independent Public Provincial Hospital at the street Arkonska 4, Szczecin and of Polish Multiple Sclerosis Society Provincial Branch in Szczecin. The analyzed group consisted of 40 persons (25 women and 15 men); the patients’ average age was 45,5 years ± 13,22. To evaluate the test group the author’s questionnaire was used. Results: During the analysis all patients were divided into three groups taking into account duration of illness. Group A – suffering from multiple sclerosis from 5 years, group B - suffering from 6 to 15 years and group C – suffering from more than 16 years. Patients sick for 5 years do not practically have problems with independent function. The patients from B and C group had the biggest problem with walking up the stairs, 84,6% of them are unable to climb the stairs independently. 30,8% of the examined patients from group B and 53,8% of the examined patients from group C were incapable of self-flexion of the knee joint in the lying down position. 30,8% of surveyed patients from group B and 23,1% of analyzed patients from group C needed assistance when walking whereas 38,5% of examined patients from group B and 46,6% patients from group C could not move independently. Conclusion: Obtained results confirm that duration of illness may be taken into consideration while functional assessment of people sick with multiple sclerosis.